Imaging features of combined hepatocellular and cholangiocarcinoma compared with those of hepatocellular carcinoma and intrahepatic cholangiocellular carcinoma in a Chinese population. Issue 5 (May 2019) - Wang, Y.; Yang, Q.; Li, S.; Luo, R.; Mao, S.; Shen, J.
Abstract : AIM: To determine the enhanced computed tomography (CT) and magnetic resonance imaging (MRI) characteristics of combined hepatocellular carcinoma and cholangiocarcinoma (cHCC-CC) in Chinese patients. MATERIALS AND METHODS: Patients with histopathologically proven cHCC-CC ( n= 54) were compared with hepatocellular carcinoma (HCC; n= 41) and cholangiocellular carcinoma (CCC; n= 41) patients. Clinical information was measured in all patients. Tumour size, tumour margins, signs of cirrhosis, pseudocapsule, capsular retraction, rim enhancement, intrahepatic biliary dilatation, portal vein thrombosis, upper abdominal lymphadenopathy, were assessed on CT and/or MRI. The dynamic pattern of enhancement was also assessed. RESULTS: The majority (81.5%) of cHCC-CC patients had positive hepatitis B serology. The presence of cirrhosis and tumour blood vessels was comparable in cHCC-CC and HCC, but significantly lower in CCC ( p> 0.05). The presence of ill-defined margin and regional lymphadenopathy was comparable in cHCC-CC and CCC, but significantly lower in HCC ( p> 0.05). The pseudocapsule, capsular retraction, biliary dilatation, rim enhancement, and abnormal perfusion were significantly different between the three types of lesions, with cHCC-CC being intermediate between HCC and CCC. Nearly half of the cHCC-CC tumours (25; 46.3%) showed the wash-in and wash-out enhancement pattern; the gradual, persistent, and mixed patterns were seen in 12 (22.2%), 5 (9.3%), and 12 (22.2%) tumours, respectively. CONCLUSION: The majority of cHCC-CC tumours occur against a background of positive hepatitis B serology and cirrhosis. Imaging findings vary widely between cHCC-CC tumours. In the present series, the enhancement pattern of cHCC-CC tumours was HCC-like in most cases.